Stress and Depression in COVID-19 Pandemic among the People Sisaket Province - Sompunga, Wanida; Phuipha, Thiranan (Journal of The Royal Thai Army Nurses, 2023)
A Retrospective descriptive study aims to determine the Stress and Depression in COVID-19 Pandemic among the People Sisaket Province. Target population is people above 15 years old and was chosen by purposive sampling from people whom answering the COVID-19 mental health questionnaire from department of mental health’s program called in “MENTAL HEALTH CHECK IN” during April 2021 total of 15,310. Method, the data was conducted by questionnaire that was developed by department of mental health which included 1) Personal data 2) Risk factors 3) Stress test (ST5), Patient health questionnaires to determine the depression which consist of 2Q and 9Q. Statistical calculations method used are frequency distributions, percentages and regression analysis. Result reveal that 15.90% of People Sisaket Province have stress and 1.36% have depression. Sex (especially female), history of mental health illness or taking anti-psychotic medications, patient infected COVID-19, people under state quarantine, unemployed people, people with financial problems, people with low income or with liability and family with bedridden patient. These are risk factors that associated with stress, and sex (female), age (60 years old above) and history of mental health illness or taking anti-psychotic medications, unemployed people, people with financial problems, people with low income or with liability and family with bedridden patient. These are risk factors associated with depression. Statistically significant p<.05.